The prevalence of functional dyspepsia using Rome III Questionnaire among adult patients attending Klinik Rawatan Keluarga, Hospital Universiti Sains Malaysia - Wahab , Noriza (2011)
Introduction: Functional Dyspepsia is one of the Functional Gastro Intestinal Disease in which there is no specific organic and pathological cause can be identified. It’s prevalence is sparse as it requires an endoscopic examination and also due to the different criteria used in different studies. Objectives: The aims of this study were to determine the prevalence of functional dyspepsia (FD) and its associated factors Methodology: This cross sectional study was conducted at Klinik Rawatan Keluarga, Hospital Universiti Sains Malaysia. The study period started on 1st December 2009 till 31st March 2010. Self administered Bahasa Malaysia version of Rome III questionnaire was used . Endoscopic examination was performed in order to exclude the organic cause of dyspepsia among patients who fulfill the criteria for Functional Dyspepsia. The diagnosis of Functional Dyspepsia was made based on the normal endoscopic finding. Results: A total of 192 patients were recruited and 32 who did not complete the questionnaires and refused endoscopy were excluded. Out of 160 patients, the prevalence of FD was 10% (n= 16). About 68% of the Functional Dyspepsia patients (n= 11) had Epigastric Pain Syndrome (EPS) and 32% of them ( n=5) were those who had mix symptoms of Post prandial Distress Syndrome and EPS. There were significant association between overweight (BMI 28 vs 25 kg/m², p<0.05), being married (p<0.05) and also having psychosocial symptoms (p< 0.05) with Functional Dyspepsia in univariate analysis. Multivariate analysis showed psychosocial symptoms (OR 3.76, 95%CI (1.01- 13.99)) and currently married (OR 8.08,95%CI (1.03-63.51)) were predictive of functional dyspepsia. Conclusion: This study supported that psychosocial symptoms were related with FD. As most of the patients who had Functional Dyspepsia were married, this could have attributed the significant association between marital status and Functional Dyspepsia.